Patient and carer access to medicines at end of life: the ActMed mixed-methods study - Sue Latter; Natasha Campling; Jacqueline Birtwistle; Alison Richardson; Michael I Bennett; David Meads; Alison Blenkinsopp; Liz Breen; Zoe Edwards; Claire Sloan; Elizabeth Miller; Sean Ewings; et al. (NIHR Journals Library, 2022)
Background: Patient access to medicines at home during the last 12 months of life is critical for effective symptom control, prevention of distress and unplanned admission to hospital. The limited evidence suggested problems with different components of service delivery and, to the best of our knowledge, the impact of innovations in end-of-life service delivery has remained unevaluated. Objective: To provide an evaluation of patient and carer access to medicines at end of life within the context of models of service delivery. Design and data sources: The study used a multiphase mixed-methods design, comprising (1) a systematic literature review; (2) an online questionnaire survey of health-care professionals delivering end-of-life care; (3) evaluative mixed-method case studies of service delivery models, including cost and cost-effectiveness analysis; (4) interviews with community pharmacists and pharmaceutical wholesalers and distributors; and (5) an expert consensus-building workshop. Setting: Community and primary care end-of-life services in England. Participants: Health-care professionals delivering end-of-life care and patients living at home in the last 12 months of life and their carers. Results: A systematic review identified a lack of evidence on service delivery models and patient experiences of accessing medicines at end of life. A total of 1327 health-care professionals completed an online survey. The findings showed that general practitioners remain a predominant route for patients to access prescriptions, but nurses and primary care-based pharmacists are also actively contributing. However, only 42% of clinical nurse specialists and 27% of community nurses were trained as prescribers. The majority (58%) of prescribing nurses and pharmacists did not have access to an electronic prescribing system. Health-care professionals' satisfaction with access to shared patient records to facilitate medicines access was low, with 39% of health-care professionals either not at all or only slightly satisfied. Respondents perceived that there would be a significant improvement in pain control if access to medicines was greater. Case studies (n = 4) highlighted differences in speed and ease of access to medicines between service delivery models. Health-care professionals' co-ordination facilitated the access process. The work of co-ordination was frequently burdensome, for example because general practitioner services were hard to access or because the stock of community pharmacy medicines was unreliable. Prescription cost differentials between services were substantial when accounting for the eligible population over the medium term. The supply chain generally ensured stocks of palliative medicines, but this was underpinned by onerous work by community pharmacists navigating multiple complex systems and wholesaler interfaces. Limitations: Patient records lacked sufficient detail for timelines to be constructed. Commissioners of community pharmacy services and wholesalers and distributors were difficult to recruit. Conclusions: Accessing medicines required considerable co-ordination work. Delays in access were linked to service delivery models that were over-reliant on general practitioners prescribing, unreliable stocks of community pharmacy medicines and clinical nurse specialists' lack of access to electronic prescribing. Key issues were relationships and team integration, diversifying the prescriber workforce, access to shared records and improved community pharmacy stock. Future work: Further research should consider policy and practice action for nursing and pharmacy services to fulfil their potential to help patients access medicines, together with attention to improving co-ordination and shared electronic records across professional service interfaces. Study registration: This study is registered as CRD42017083563 and the trial is registered as ISRCTN12762104. Funding: This project was funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme and will be published in full in Health and Social Care Delivery Research; Vol. 10, No. 20. See the NIHR Journals Library website for further project information.